The Supply Chain Management of Islamic and Conventional Banks; Evidence from Indonesian Case - Imronudin Imronudin; Henry Dwi Wahyudi (International Journal of Supply Chain Management, 2020)
Abstract— The present study aims to examine the idea of supply chain management in the financial institutions like banks in the region of Indonesia. After the detailed examination of existing literature current research work has developed a model for the supply chain in financial perspective with its physical implication as well. This study use panel or pooled data taken from annual report of Islamic and conventional banks in Indonesia during 2012-2017 period and consist of 10 Islamic and 24 conventional banks. Pooled regression is used to estimate the effect of bank-specific such as profitability, growth, tangibility, earning volatility and size on supply chain management. The finding of this study shows that profitability and growth have positive and significant effect on supply chain management, while size and tangible asset have negative impact on it of conventional banks. Earning volatility does not have any influence on supply chain management both for Islamic and conventional banks. In general, there is no significant explanatory variables which have significant influence on supply chain management of Islamic banks except growth variable which have marginal impact on supply chain management decision. In the future, this research can be developed by using different measure of earning volatility.